Example: 2x+2y=8 and 3y+2x=6
Okay so u first want to put on of the equations into a y= form. So let's use 3y+2x=6. Subtract 2x from both sides. 3y=6-2x divide by 3. Y= 6-2/3x or y= -2/3x + 6. Now just plug this new equation in for Y since "y=" into the other equation.
2x + 2(-2/3x + 6) = 8.
Then you would distribute the 2 into the parenthesis and simplify to solve for x.
After you solve for x, plug x into one of the original equations to find y.
The answer would be $15
All you need to do is multiply each one by .4 and see which one equals 6.
15 x .4 =6
Hope this helps!
Notice that both A and B are multiplied by (1/2).
Thus, the given expression can be re-written as [(1/2)(A+B)]^2.
Square the (1/2) and the (A+B) separately, and then multiply together the resulting squares:
(1/4)(A^2 + 2AB + B^2)
Answer: No
Step-by-step explanation:
Is 1/4 (8y -12) equivalent to 2y - 12? No. 1/4 (8y-12) equals out to 2y-3 not 2y-12. To solve the system of equations below, grace isolated the variable y in the first equation and then substituted into the second equation. what was the resulting equation? 3y=12x x^2/4+y^2/9=1
Answer:
The first one is you don't make eye contact with others. And the second one is false
Step-by-step explanation: